The role of shame in the relationship between bullying and self-harm in portuguese adolescents. (13th April 2021) - Bento, C.; Pereira, A.T.; Oliveira, M.; Cartaxo, T.; Carvalho, F.; Macedo, A.
Abstract : Introduction: Bullying consists in acts of intentional and repeated physical or psychological violence, completed by an individual or a group of individuals, provoking pain, distress and shame. Currently, it is considered a serious problem with health implications in adolescents. Shame is a self-conscious, multifaceted and socially focused emotion that relates to a negative self-assessment. Objectives: The study aim was to investigate the mediating role of Shame in the relationship between Bullying and Self-harm and Suicide Ideation in Portuguese adolescents. Methods: 346 adolescents (58.4% girls), aged 15.32±1.193 from public and private schools (9 th to 12 th grades) in Coimbra, answered the validated Portuguese versions of the Bullying Questionnaire, the Other as Shame Scale for Adolescents and the Self-Harm and Suicidal Ideation Questionnaire. For data analysis the SPSS 26 and Macro Process (Hayes 2020) was used. Results: Bullying Victimization had a prevalence of 18.78%. Girls and boys significantly differ in Bullying Victimisation, Self-Harm, Suicidal Ideation and Shame mean scores (all p<.05). In girls, Bullying Victimisation was correlated with Shame and Suicidal Ideation. The mediation analysis showed that, in girls, Shame partially mediated the relationship between Bullying and Suicidal Ideation (p<.001). We didn't find these results in boys. Conclusions: Bullying is a global problem that needs to be addressed. Adolescents of today are the adults of tomorrow. In a physical growth and mental maturation phase, it is urgent to avoid disruptors which lead to psychopathology. Our results corroborate that Shame can be a harmful factor in Bullying with deleterious consequences in adolescents.